2010
DOI: 10.1089/jpm.2009.0399
|View full text |Cite
|
Sign up to set email alerts
|

Implementing WHO Recommendations for Palliative Care into Routine Lung Cancer Therapy: A Feasibility Project

Abstract: Though some degree of development towards a better understanding of PC competencies and the "early integration" approach could be demonstrated, the adoption of the WHO recommendation alone did not suffice to integrate PC into routine cancer care early in the course of the illness. Therefore, the development of disease specific guidelines is advocated by our working group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 30 publications
2
35
0
1
Order By: Relevance
“…A number of studies from single centres looked at better access to care, acceleration of diagnostic steps, aspects of thoracic surgery, radiotherapy and integration of palliative care [23,25,[41][42][43]. In two independent studies by SALATI et al [44] and SCHWARZBACH et al [45], the implementation of a clinical pathway for thoracic surgery led to a reduction of hospital stay without negatively influencing readmission rates.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies from single centres looked at better access to care, acceleration of diagnostic steps, aspects of thoracic surgery, radiotherapy and integration of palliative care [23,25,[41][42][43]. In two independent studies by SALATI et al [44] and SCHWARZBACH et al [45], the implementation of a clinical pathway for thoracic surgery led to a reduction of hospital stay without negatively influencing readmission rates.…”
Section: Resultsmentioning
confidence: 99%
“…Here, green flags and red flags have been devised to develop standard operating procedures for an early integration approach. 29 Temel et al 30 were able to show that early palliative care led to significant improvements in both quality of life and mood in addition to prolonging life. That participants in our study see the integration as rather late in the disease trajectory might illustrate how misperceptions still exist and how a lack of information regarding palliative care, as identified earlier, 9,31 remains.…”
Section: (Expanded Disability Status Scale [Edss]mentioning
confidence: 99%
“…Paradigmatically, the SOP for comprehensive breast cancer therapy is presented here, since its therapeutic algorithm differs substantially from the SOPs for other solid tumors such as lung cancer [10,12] because of the clinical characteristics of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of relevant pilot project data revealed that this approach was too vague to serve as a general clinical guideline to successfully implement early integration of PC [10,11]. As a consequence, in addition to inclusion in administrative directives and establishment of a PCST, we decided to develop standard operating procedures (SOPs) as diseasespecific guidelines to i) define disease-specific points in the Decision for Disease-Specific PC SOPs Because of the experiences described above, we decided that the sole adoption of the WHO recommendation in the administrative guidelines plus the provision of a PCST in addition to the preexisting home care service and inpatient ward did not suffice to integrate PC early enough.…”
Section: Time and Place Of Pc Integrationmentioning
confidence: 99%